SOCIAL CHANGE AND CHARACTER EDUCATION IN THE DIGITAL ERA: PERUBAHAN SOSIAL DAN PENDIDIKAN KARAKTER DI ERA DIGITAL - I Putu Sriartha; Wayan Mudana; I Made Pageh; I DEWA AYU EKA PURBA DHARMA TARI; Putu Abda Ursula; Ni Ketut Erawati (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The social changes that occur in society are influenced by the development of digital technology and have had a profound impact on the education system, school culture, and quality of education. This article aims to analyze the dynamics of social change in education, its impact on school culture, as well as the challenges and opportunities that arise in efforts to improve the quality of education in the digital era. The main focus of this research is character education, which is becoming increasingly relevant amid rapid technological advancements. Character education in the digital age focuses not only on the development of moral values, but also on the formation of the social and emotional intelligence necessary to interact ethically in cyberspace. Through a literature review, this article finds that in order to adapt to social and technological changes, education systems need to transform, create an inclusive environment, and ensure that technology is used as a tool to improve the quality of education, without neglecting social and ethical values. This research concludes that character education in the digital era requires a holistic approach that integrates technology with the teaching of moral and social values to shape the young generation that is ready to face global challenges.